P112 SMILE: Sustaining Medical Education In a Lockdown Environment.Using social media to develop a free online access medical education platform during lockdown. (8th April 2021) - Pascoe, John; Foster, Paul; Quddus, Muntasha; Kosti, Angeliki; Guest, Francesca; Stevens, Sian; Bamford, Richard; Coulston, James; Pascoe, John
Abstract: Introduction: SMILE is a free online access medical education (FOAMEd) platform created by two UK surgical trainees and a medical student that delivered over 200 medical lectures during lockdown. Method: The role of Social Media in the development of SMILE was interrogated using a survey sent to all SMILE participants and by analysing activity on SMILE social media platforms. Results: 1306 students responded to the online survey with 57.2% saying they heard of SMILE through Facebook. Engagement using facebook remained highest with 13, 819 members, over 800 user comments and >16, 000 user reactions. 4% of the students heard of SMILE through Twitter or Instagram. Facebook analytics revealed the highest level of traffic when lectures were most commonly held suggesting students used Facebook to access lectures. Other educators were able to find SMILE on social media, leading to collaborations with other platforms. Throughout the survey many mentioned how social media created and maintained a community of medical students enhancing group-based learning Conclusions: We demonstrate that social media platforms provide popular and cost-effective methods to promote, sustain & deliver medical education for students and educators.